PEDOMAN PEMIDANAAN DALAM KONTEKS PEMBAHARUAN HUKUM PIDANA INDONESIA DIMASA MENDATANG - Dwi Okta Ariyanti; Muhammad Ramadhan (Kajian Hukum, 2022)
Abstract Criminal law reform, in this case relates to the reorientation of the purpose of punishment. It is important to see what the goals and achievements are to be expected from a reform process in criminal law. This study aims to analyze the policy formulation of criminal law guidelines in Indonesia as well as to analyze sentencing guidelines in the context of reforming Indonesian criminal law in the future. This research was conducted using a normative juridical approach, which is an approach based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research. This approach is also known as the library approach, namely by studying books, laws and regulations and other documents related to this research. Sentencing guidelines are basic provisions that provide direction, which determine the imposition of a criminal, this is a guide for judges in implementing and imposing a sentence. Because these guidelines are basic guidelines, they are part of legislative policy